Cardiac Implications of Adenotonsillar Hypertrophy and Obstructive Sleep Apnea in Pediatric Patients: A Comprehensive Systematic Review - Marco Zaffanello; Refika Hamutcu Ersu; Luana Nosetti; Giulio Beretta; Massimo Agosti; Giorgio Piacentini (MDPI AG, 2024)
This review investigates the relationship between pediatric obstructive sleep apnea, often associated with adenotonsillar hypertrophy, and cardiovascular health, particularly pulmonary hypertension. We conducted a comprehensive literature search using electronic databases, including Medline Pub-Med, Scopus, and the Web of Science. The study analyzed a total of 230 articles and screened 48 articles, with 20 included in the final analysis, involving 2429 children. The PRISMA flowchart visually illustrates the selection process, and the ROBINS-E and -I tools help ensure the reliability and validity of the evidence produced by these studies. These studies explored various aspects, including the severity of obstructive sleep apnea, cardiac anomalies, cardiac stress markers, risk factors for pulmonary hypertension, and the impact of adenoidectomy and tonsillectomy on cardiac function. The research found that adenotonsillar hypertrophy and obstructive sleep apnea are significant risk factors for cardiovascular complications, especially pulmonary hypertension, in children. Adenoidectomy and tonsillectomy may provide effective treatments. Following adenoidectomy in relation to obstructive sleep apnea, there appears to be a reduction in mean pulmonary artery pressure during echocardiographic examination. However, the efficacy of these procedures can vary based on the severity of obstructive sleep apnea and individual cardiac conditions. The study also identified concerns regarding data bias. The authors emphasize the need for well-designed clinical studies, including both healthy patients with adenotonsillar hypertrophy and vulnerable children with genetic disorders, to ensure that clinical decisions are based on solid scientific evidence.